Identifying Sustainable Supply Chain Indicators in the Dairy Industry with a Foresight Approach - Abedini, Meysam; Mohammad Alipour, Narges; Shah Mansouri, Ashraf; Rabie, Mahnaz (Management Strategies and Engineering Sciences, 2025)
This study aimed to identify the key indicators of a sustainable supply chain in the Iranian dairy industry using a foresight-based qualitative approach. The research employed a qualitative methodology rooted in foresight thinking to explore the multidimensional aspects of sustainability in the dairy supply chain. Participants were selected through purposive and snowball sampling and included 11 individuals from three stakeholder groups: academic experts, industry professionals, and independent stakeholders such as consumers and researchers. Semi-structured in-depth interviews were conducted to gather insights into economic, social, environmental, legal, and ethical factors affecting sustainability. Data were analyzed using thematic analysis in MAXQDA software, following a six-step coding process: familiarization with data, initial coding, theme development, theme review, definition and naming of themes, and report generation. Theoretical saturation was reached after the ninth interview, and two additional interviews confirmed data saturation. Two overarching themes were extracted from the interviews: “Drivers” and “Dairy Supply Chain Sustainability.” The Drivers theme included five organizing categories—economic, social, environmental, legal, and ethical factors—each comprising several foundational indicators such as cost reduction, social responsibility, renewable energy use, regulatory compliance, and ethical leadership. The Dairy Supply Chain Sustainability theme featured six organizing themes: sustainable sourcing, sustainable management, sustainable culture, sustainable customer orientation, strategic sustainability planning, and dairy-specific sustainability practices. These themes encompassed a total of 62 basic indicators, providing a comprehensive framework for assessing and enhancing sustainability in the dairy industry. The findings highlight the need for an integrated, multi-dimensional strategy for achieving sustainability in the dairy supply chain, emphasizing foresight, stakeholder collaboration, ethical governance, and environmental responsibility. The proposed conceptual model can guide both strategic planning and policy formulation in dairy supply chain sustainability.